The Evaluation of Ovarian Function Recovery Following Treatment of Primary Ovarian Insufficiency: A Systematic Review - Kuang, Xiaojun; Tang, Yongzhe; Xu, Hong; Ji, Min; Lai, Dongmei (Frontiers in Endocrinology, 2022)
Background: Primary ovarian insufficiency (POI) is gaining awareness as prevalence increases and has an extremely negative effect on patients. To date, several therapies have been designed to treat POI, but the conclusions are conflicting related in part to inconsistent evaluation methods. Thus, we explore a multi-index of ovarian function assessment method to evaluate the recovery of ovarian function after various therapies to evaluate effectiveness in a more comprehensive manner. Aim: The purpose of this review is to assess the effectiveness of various therapies to recover ovarian function in patients with POI. The primary outcome measures were anti-Müllerian hormone (AMH) levels, follicle stimulating hormone (FSH) levels, and antral follicle count (AFC). The secondary outcomes included the change of mean ovarian volume, menstruation recovery, and pregnancy rate. Methods: Our systematic searching including PubMed, Web of Science, Cochrane, and Embase databases was conducted to find all human clinical trial articles published from January 2000 to April 2021 and related to POI treatment, including the keywords: POI, AFC, and hormones. All prospective and retrospective studies exploring ovarian function recovery that include AFC, AMH levels, and FSH levels evolution throughout treatment were included. All patients included in the studies met the POI criteria described by the European Society for Human Reproductive Embryology (ESHRE) guideline. Results: Six studies were selected based on the criteria, including one randomized controlled trial and five observational studies. Among them, two studies focused on the intraovarian platelet-rich plasma (PRP) infusion treatment, two studies focused on the dehydroepiandrosterone (DHEA) supplements, one study focused on the hormone replacement therapy (HRT), and one study focused on autologous adipose-derived stromal cells (ADSCs) treatment. There was insufficient scientific evidence that any approach could help ovarian function recovery in patients with POI because the ovarian function markers in each study had inconsistent changes. 26 patients (6.2%) had reported spontaneous pregnancy in total. Conclusion: Serum AMH levels, FSH levels, and AFC are sensitive indicators and reflect the evolution of ovarian function. Large randomized controlled trials are necessary, and the data on ovarian function should be collected comprehensively to evaluate the effectiveness of a variety of treatments.